Oxygen evolution reaction catalyst as well as preparation method and application thereof

By incorporating iridium and other noble metals into the cerium oxide lattice, a highly stable and active oxygen evolution reaction catalyst was prepared, solving the problems of scarcity and poor stability of existing catalysts and enabling efficient operation of proton exchange membrane water electrolysis.

CN120967430APending Publication Date: 2025-11-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511239343.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

In existing proton exchange membrane water electrolysis, catalysts for the oxygen evolution reaction at the anode, such as iridium oxide, are scarce and costly. Carbon materials are prone to oxidation and failure, and cobalt-based oxides dissolve in acidic media, resulting in poor catalyst stability and limiting their application.

Method used

A noble metal-doped cerium oxide catalyst is prepared by incorporating iridium and another metal, such as ruthenium, gold, or platinum, into the cerium oxide lattice in the form of single atoms via a solvothermal evaporation method. This forms a two-component noble metal-doped cerium oxide catalyst, which avoids noble metal agglomeration and improves stability.

Benefits of technology

It achieves high stability and high activity in proton exchange membrane water electrolysis, with high utilization of precious metals, low cost, and suitability for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120967430A_ABST
    Figure CN120967430A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oxygen evolution reaction catalysts, and particularly relates to an oxygen evolution reaction catalyst and a preparation method and application thereof. The oxygen evolution reaction catalyst is a noble metal doped cerium oxide catalyst, the noble metal is a bi-component metal, the bi-component metal is doped into a cerium oxide crystal lattice in a monatomic form, and one of the bi-component metal is iridium. According to the metal oxide catalyst doped with the two-component precious metal, the intrinsic activity of the catalyst and the utilization rate of the precious metal are improved, and the metal oxide catalyst doped with the two-component precious metal shows good durability when being used in a catalytic layer of a proton exchange membrane water electrolysis anode and has a wide practical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of oxygen evolution reaction catalysts, and particularly relates to an oxygen evolution reaction catalyst and a preparation method and application thereof. BACKGROUND

[0002] Water electrolysis is an efficient and clean way to store and convert excess renewable energy. Among various methods of water electrolysis, proton exchange membrane water electrolysis is outstanding due to its high current density, high hydrogen purity, fast response speed and strong operability. At present, the development of proton exchange membrane water electrolysis is limited due to the scarcity and irreplaceability of iridium oxide catalyst for anode oxygen evolution reaction. Therefore, it is imperative to develop a high-activity and low-cost oxygen evolution reaction catalyst.

[0003] Single-atom catalysts exhibit better catalytic activity than nanoparticles or sub-nanometer clusters due to their high atom utilization efficiency. Reducing iridium, which is at the top of the volcano plot of oxygen intermediate binding energy, to single-atom size can greatly reduce the cost of proton exchange membrane water electrolysis without sacrificing activity and stability.

[0004] Currently, single-atom catalysts for anode oxygen evolution reaction in proton exchange membrane water electrolysis mainly include metal-nitrogen-coupled carbon materials and metal-oxygen-coupled metal oxide materials. Metal-nitrogen-coupled carbon materials fix iridium atoms on carbon supports by introducing nitrogen-containing ligands through easily functionalized carbon sites, resulting in unique metal coordination centers and extremely high oxygen evolution activity. Meanwhile, using highly conductive carbon materials such as graphene as carriers can also promote charge transfer in the oxygen evolution reaction, further improving the efficiency of acidic water electrolysis. However, carbon materials are easily oxidized and lose their effectiveness in the strong oxidative environment of proton exchange membrane water electrolysis, making them unsuitable for long-term use in the anode catalyst layer of proton exchange membrane water electrolysis. Metal-oxygen-coupled metal oxide materials are mainly fourth-period transition metal oxides with high abundance and low cost. Cobalt-based oxides such as spinel cobalt oxide are used as carriers for iridium single atoms due to their flexible composition and adjustable structure. By simply immersing iridium salt and pyrolyzing metal organic frameworks or zeolite imidazolate frameworks, atomically dispersed iridium atom-doped cobalt oxide can achieve mass activity several orders of magnitude higher than iridium oxide. However, cobalt-based oxides will dissolve severely in acidic media, leading to collapse of the crystal structure and hindering their application in proton exchange membrane water electrolysis. SUMMARY

[0005] The purpose of the present application is to provide an oxygen evolution reaction catalyst and a preparation method and application thereof, which has good stability, simple preparation process and good industrial application prospect.

[0006] To achieve the above purpose, the technical solutions of the present application are as follows: The first aspect of the present application provides an oxygen evolution reaction catalyst, the catalyst being a noble metal doped ceria catalyst, wherein the noble metal is a two-component metal, the two-component metal is doped into the ceria lattice in the form of a single atom, and one of the metals in the two-component metal is iridium.

[0007] Optionally, the other metal in the two-component metal is ruthenium, gold or platinum.

[0008] Optionally, in the catalyst, the content of iridium is 3-7.5 wt.%, and the content of the other metal is 0.1-3 wt.%.

[0009] The second aspect of the present application provides a preparation method of the above-mentioned oxygen evolution reaction catalyst, comprising the following steps: (1) dispersing a double noble metal precursor and a cerium ion salt in water to obtain a precursor solution; (2) dividing the precursor solution obtained in step (1) into equal volumes and evaporating the solvent to obtain the oxygen evolution reaction catalyst.

[0010] Optionally, in step (1), the metal iridium precursor of the double noble metal precursor is at least one of chloroiridic acid and iridium trichloride, and the other metal precursor is one of ruthenium trichloride, chloroplatinic acid and chloroauric acid; In step (1), in the precursor solution, the concentration of the metal iridium precursor is 0.01-4 mmol / L -1 , the concentration of the other metal precursor is 0.01-6.3 mmol / L -1 , and the concentration of the cerium ion salt is 82-92 mmol / L -1 .

[0011] In step (2), the partition volume of the equal volume partition is 5-300 μL.

[0012] In step (2), the heating temperature of the evaporation solvent is 200-300°C, and the heating time is 12-24 h.

[0013] The third aspect of the present application provides an oxygen evolution electrode comprising the above-mentioned catalyst, wherein the loading of Ir in the oxygen evolution electrode is 0.05-0.2 mg / cm 2 , and the loading of the other metal is 0.01-0.06 mg / cm 2 .

[0014] The fourth aspect of the present application provides an application of the above-mentioned oxygen evolution electrode in a proton exchange membrane water electrolysis.

[0015] Optionally, the proton exchange membrane comprises at least one of Nafion 117, Nafion 115 and Nafion 212.

[0016] The beneficial effects of the present application are: 1) The present application selects rare earth metal oxide cerium oxide as the substrate, and the unique Ce 3+ / Ce 4+ Redox pair provides an anchoring site for atomic dispersion of noble metals, by incorporating metal iridium components into the cerium oxide lattice, and anchoring another metal component (ruthenium, gold or platinum) into the cerium oxide lattice, a double-component noble metal doped cerium oxide catalyst is obtained. The catalyst of the present application has excellent electronic adjustment ability and shows excellent catalytic stability in proton exchange membrane water electrolysis anode.

[0017] 2) The present application adopts a solvent thermal evaporation preparation method, by controlling the content of noble metal in the precursor solution and the volume of evaporation solvent, avoiding the agglomeration of noble metal, and obtaining an atomic dispersion of double-component noble metal doped cerium oxide catalyst.

[0018] 3) The present application has high raw material conversion rate, low cost, mild conditions, simple operation, and good catalyst stability, and has strong practical applicability.

[0019] 4) The oxygen evolution reaction catalyst prepared by the present application can reach 10mAcm -2 @500h stability in 0.1M HClO4 in a three-electrode system, and can reach 50mA cm -2 @500h stability in a proton exchange membrane water electrolysis cell, providing a feasible method for improving the utilization rate and durability of noble metal catalysts in proton exchange membrane water electrolysis. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 X-ray diffraction pattern of the oxygen evolution reaction catalyst obtained in Example 1 and Comparative Example 1; Figure 2 Transmission electron microscope image of the oxygen evolution reaction catalyst obtained in Example 1; Figure 3 High-angle annular dark field scanning transmission electron microscope image of the oxygen evolution reaction catalyst obtained in Example 1; Figure 4 High-angle annular dark field scanning transmission electron microscope image and element mapping of the oxygen evolution reaction catalyst obtained in Example 1; Figure 5 Linear sweep voltammogram of the oxygen evolution reaction catalyst obtained in Examples 1-7 and Comparative Examples 1-4 in 0.1M HClO4; Figure 6 Stability curve of the proton exchange membrane water electrolysis of the oxygen evolution reaction catalyst obtained in Example 1. DETAILED DESCRIPTION

[0021] The present application will be described in detail below with reference to examples, but the present application is not limited to these examples.

[0022] Unless otherwise specified, the raw materials in the examples of the present application are purchased through commercial channels. H2IrCl6·6H2O, IrCl3·nH2O, RuCl3·nH2O, H2PtCl6·6H2O and HAuCl4·4H2O are purchased from Kunming Platinax Metal Material Co., Ltd.; Ce(NO3)2·6H2O and (NH4)2Ce(NO3)6 are purchased from Aldrin Reagent Co., Ltd.; HCIO4 is purchased from Tianjin Zhengcheng Chemical Co., Ltd.; Nafion 117 membrane, Nafion 115 membrane and Nafion 212 membrane are purchased from DuPont; Pt / C catalyst is purchased from Johnson Matthey Catalyst Co., Ltd.; commercial IrO2 is purchased from Heraeus Noblemetal Technology Co., Ltd.

[0023] In the examples of the present application, the X-ray powder diffraction phase analysis of the sample is performed by using Empyrean-100 X-ray diffractometer of Panalytical Co., Ltd., Netherlands, Cu target, Kα radiation source (λ = 0.15418 nm), voltage 40 kV, current 40 mA. The internal fine structure analysis of the sample is performed by using JEM-2100 transmission electron microscope of Japan Electron Co., Ltd. The fine atomic arrangement observation of the sample is performed by using JEM-ARM200F spherical aberration correction scanning transmission electron microscope of Japan Electron Co., Ltd. The oxygen evolution reaction performance evaluation of the sample in a three-electrode system is performed by using Interface1010E electrochemical workstation of Gamry Instruments.

[0024] Example 1 454.8 mg of Ce(NO3)3·6H2O, 15.1 mg of RuCl3·nH2O and 25.21 mg of H2IrCl6·6H2O are dissolved in 12 mL of H2O, and a uniform precursor solution is obtained by magnetic stirring. The precursor solution is evenly divided into 300 μL each and heated in a drying oven at 200 ℃ for 12 h. The obtained powder is an iridium-ruthenium-doped cerium oxide oxygen evolution reaction catalyst, and the mass percentage contents of iridium and ruthenium in the catalyst are 7.36 wt.% and 1.35 wt.% respectively.

[0025] As shown in FIG. 1, the X-ray diffraction pattern shows that the catalyst obtained in Example 1 has good crystallinity, and there are diffraction peaks of (111), (200) and (220) crystal planes corresponding to the face-centered cubic fluorite phase cerium oxide, and there are no characteristic peaks of iridium and iridium oxide. Figure 1 Figure 2 ​As shown, high resolution transmission electron microscopy (HRTEM) images observed lattice fringes corresponding to the crystal planes of the catalyst obtained from Example 1. As shown in FIG. 2B, the high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images showed that the catalyst obtained from Example 1 had dense and isolated high-contrast bright spots distributed in the crystal lattice, indicating that iridium atoms were uniformly anchored in the cerium oxide lattice, forming a uniform doped phase. As shown in FIG. 2C, the simultaneous scanning transmission electron microscopy-energy dispersive spectroscopy (STEM-EDS) element distribution Mapping images also showed that the iridium and ruthenium elements were uniformly distributed and had no bright clusters in the images, proving that the iridium and ruthenium elements in the catalyst were uniformly doped into the cerium oxide lattice. Figure 3 As shown, high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images showed that the catalyst obtained from Example 1 had dense and isolated high-contrast bright spots distributed in the crystal lattice, indicating that iridium atoms were uniformly anchored in the cerium oxide lattice, forming a uniform doped phase. As shown in FIG. 2B, the high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images showed that the catalyst obtained from Example 1 had dense and isolated high-contrast bright spots distributed in the crystal lattice, indicating that iridium atoms were uniformly anchored in the cerium oxide lattice, forming a uniform doped phase. As shown in FIG. 2C, the simultaneous scanning transmission electron microscopy-energy dispersive spectroscopy (STEM-EDS) element distribution Mapping images also showed that the iridium and ruthenium elements were uniformly distributed and had no bright clusters in the images, proving that the iridium and ruthenium elements in the catalyst were uniformly doped into the cerium oxide lattice. Figure 4 As shown, high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images showed that the catalyst obtained from Example 1 had dense and isolated high-contrast bright spots distributed in the crystal lattice, indicating that iridium atoms were uniformly anchored in the cerium oxide lattice, forming a uniform doped phase. As shown in FIG. 2B, the high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images showed that the catalyst obtained from Example 1 had dense and isolated high-contrast bright spots distributed in the crystal lattice, indicating that iridium atoms were uniformly anchored in the cerium oxide lattice, forming a uniform doped phase. As shown in FIG. 2C, the simultaneous scanning transmission electron microscopy-energy dispersive spectroscopy (STEM-EDS) element distribution Mapping images also showed that the iridium and ruthenium elements were uniformly distributed and had no bright clusters in the images, proving that the iridium and ruthenium elements in the catalyst were uniformly doped into the cerium oxide lattice.

[0026] The oxygen evolution reaction catalyst prepared in Example 1 was subjected to electrochemical testing, and a 0.1M HCIO4 solution saturated with N2 at 25°C was used as the electrolyte, a 1×1 cm 2 platinum sheet was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and a 5mm-diameter glassy carbon rotating disk electrode was used as the working electrode. The working electrode catalyst slurry was prepared by dispersing 4 mg of the catalyst and 2 mg of carbon black in 475 μL of anhydrous ethanol and 25 μL of a 5 wt.% Nafion solution and ultrasonically dispersing for 1 h. The oxygen evolution reaction performance of the catalyst in 0.1M HCIO4 was compared according to the noble metal loading of 0.096 mg cm -2 (the iridium and ruthenium loadings were 0.081 mg cm -2 and 0.015 mg cm -2 , respectively), as shown in FIG. 3. Figure 5

[0027] The oxygen evolution reaction catalyst prepared in Example 1 was subjected to oxygen evolution reaction stability testing, and a 2×2 cm 2 catalyst layer was used on both sides of a Nafion 115 membrane by ultrasonic spraying; the catalyst slurry was prepared in a mass ratio of catalyst: 5 wt.% Nafion solution: isopropyl alcohol of 1:6.7:180; the anode used the oxygen evolution reaction catalyst prepared in Example 1, and the cathode used Pt / C containing 50 wt.% Pt; a platinum-coated titanium felt was used as the anode-side diffusion layer, and carbon paper was used as the cathode-side diffusion layer; the membrane electrode was sealed and hot-pressed using a polyester frame, the hot-pressing temperature was 140°C, the membrane electrode was packaged using platinum-coated titanium plates containing straight flow channels on both sides, and insulating pads were installed on the outermost layers on both sides; the electrolytic cell components were fixed by tightening bolts at the four corners, and the assembly force of the cell was 3 N·m. Deionized water was pumped at a rate of 100 mL min -1 ​The flow of water was injected into the anode side of the electrolytic cell. A heating rod was inserted into the titanium plate to maintain the temperature of the electrolytic cell at 80 °C. The heated water flow returned to the water storage tank from the anode outlet, forming a closed water circuit, and the hydrogen generated at the cathode side was discharged through the tail pipe. According to the catalyst noble metal loading of 0.12 mg cm -2 (0.1 mg cm -2 and 0.02 mg cm -2 of iridium and ruthenium, respectively) and the current density of 50 mA cm -2 , the oxygen evolution reaction stability diagram is shown in Figure 6 .

[0028] Example 2 454.8 mg of Ce(NO3)3·6H2O, 10.3 mg of RuCl3·nH2O, and 25.21 mg of H2IrCl6·6H2O were dissolved in 12 mL of H2O, and a uniform precursor solution was obtained by magnetic stirring. The precursor solution was evenly divided into 300 μL each and placed in a blast drying oven at 200 °C for heating for 12 h. The obtained powder was an iridium-ruthenium-doped cerium oxide oxygen evolution reaction catalyst. The mass percentage of iridium and ruthenium in the catalyst was 6.03 wt.% and 0.56 wt.% respectively.

[0029] The same test method as in Example 1 was used. The oxygen evolution reaction performance comparison diagram in 0.1 M HCIO4 according to the noble metal loading of 0.096 mg cm -2 (0.088 mg cm -2 and 0.008 mg cm -2 of iridium and ruthenium, respectively) is shown in Figure 5 .

[0030] Example 3 454.8 mg of Ce(NO3)2·6H2O, 20.5 mg of RuCl3·nH2O, and 25.21 mg of H2IrCl6·6H2O were dissolved in 12 mL of H2O, and a uniform precursor solution was obtained by magnetic stirring. The precursor solution was evenly divided into 300 μL each and placed in a blast drying oven at 200 °C for heating for 12 h. The obtained powder was an iridium-ruthenium-doped cerium oxide oxygen evolution reaction catalyst. The mass percentage of iridium and ruthenium in the catalyst was 7.36 wt.% and 2.51 wt.% respectively.

[0031] The same test method as in Example 1 was used. The oxygen evolution reaction performance comparison diagram in 0.1 M HCIO4 according to the noble metal loading of 0.096 mg cm -2 (0.072 mg cm -2 and 0.024 mg cm -2 of iridium and ruthenium, respectively) is shown in Figure 5 .

[0032] Example 4 454.8 mg of Ce(N03)3-6H20, 12.55 mg of H2PtCl6-6H20 and 12.65 mg of H2IrCl6-6H20 were dissolved in 12 mL of H20, and a uniform precursor solution was obtained by magnetic stirring. The precursor solution was evenly divided into 300 μL each and heated in a blast drying oven at 200°C for 12 h to obtain an iridium-platinum-doped cerium oxide catalyst for oxygen evolution reaction. The mass percentage of iridium and platinum in the catalyst was 3.95 wt.% and 3.00 wt.% respectively. The same test method as in Example 1 was used to compare the oxygen evolution reaction performance of the catalysts in 0.1 M HC104 with a noble metal loading of 0.096 mg cm -2 (the iridium and platinum loadings were 0.055 mg cm -2 and 0.041 mg cm -2 respectively). Figure 5

[0033] Example 5 454.8 mg of Ce(N03)3-6H20, 5.00 mg of H2PtCl6-6H20 and 20.20 mg of H2IrCl6-6H20 were dissolved in 12 mL of H20, and a uniform precursor solution was obtained by magnetic stirring. The precursor solution was evenly divided into 300 μL each and heated in a blast drying oven at 200°C for 12 h to obtain an iridium-platinum-doped cerium oxide catalyst for oxygen evolution reaction. The mass percentage of iridium and platinum in the catalyst was 6.83 wt.% and 0.96 wt.% respectively.

[0034] The same test method as in Example 1 was used to compare the oxygen evolution reaction performance of the catalysts in 0.1 M HC104 with a noble metal loading of 0.096 mg cm -2 (the iridium and platinum loadings were 0.084 mg cm -2 and 0.012 mg cm -2 respectively). Figure 5

[0035] Example 6 463.6 mg of Ce(N03)3-6H20, 6.40 mg of HAuCl4-4H20 and 9.96 mg of H2IrCl6-6H20 were dissolved in 12 mL of H20, and a uniform precursor solution was obtained by magnetic stirring. The precursor solution was evenly divided into 300 μL each and heated in a blast drying oven at 200°C for 12 h to obtain an iridium-gold-doped cerium oxide catalyst for oxygen evolution reaction. The mass percentage of iridium and gold in the catalyst was 3.25 wt.% and 2.73 wt.% respectively.​​

[0036] The comparison chart of oxygen evolution reaction performance in 0.1M HCIO4 according to the noble metal loading of 0.096 mg cm -2 (the iridium and gold loadings are 0.082 mg cm -2 and 0.014 mg cm -2 respectively) is shown in Figure 2. Figure 5

[0037] Example 7 463.6 mg of Ce(N03)3-6H20, 2.25 mg of HAuCl4-4H20 and 14.08 mg of H2IrCl6-6H20 were dissolved in 12 mL of H20, and a uniform precursor solution was obtained by magnetic stirring. The precursor solution was equally divided into 300 μL each and heated in a blast drying oven at 200°C for 12 h to obtain an iridium and gold doped cerium oxide catalyst. The mass percentage of iridium and gold in the catalyst was 5.98 wt.% and 1.02 wt.% respectively.

[0038] The comparison chart of oxygen evolution reaction performance in 0.1M HCIO4 according to the noble metal loading of 0.096 mg cm -2 (the iridium and gold loadings are 0.082 mg cm -2 and 0.014 mg cm -2 respectively) is shown in Figure 2. Figure 5

[0039] Comparative Example 1 480 mg of Ce(N03)3-6H20 was dissolved in 12 mL of H20, and a uniform precursor solution was obtained by magnetic stirring. The solution was equally divided into 300 μL each and heated in a blast drying oven at 200°C for 12 h to obtain a cerium oxide catalyst.

[0040] The comparison chart of oxygen evolution reaction performance in 0.1M HCIO4 according to the catalyst loading of 1 mg cm -2 is shown in Figure 3. Figure 5

[0041] Comparative Example 2 429.6 mg of Ce(N03)2-6H20 and 50.67 mg of H2IrCl6-6H20 were dissolved in 12 mL of H20, and a uniform precursor solution was obtained by magnetic stirring. The solution was equally divided into 300 μL each and heated in a blast drying oven at 200°C for 12 h to obtain an iridium doped cerium oxide catalyst. The mass percentage of iridium in the catalyst was 4.96 wt.%. ​​​

[0042] The same test method as in Example 1 was used to compare the oxygen evolution reaction performance of the catalysts in 0.1 M HCIO4 with a noble metal iridium loading of 0.096 mg cm -2 -2. Figure 5

[0043] Comparative Example 3 454.8 mg of Ce(NOs)2-6H2O and 62.1 mg of RuCl3-nH2O were dissolved in 12 mL of H2O, and a uniform precursor solution was obtained by magnetic stirring. The solution was divided into 300 μL aliquots, which were heated in a blast drying oven at 200°C for 12 h. The resulting powder was a ruthenium-doped cerium oxide catalyst, and the mass percentage of ruthenium in the catalyst was 4.14 wt.%.

[0044] The same test method as in Example 1 was used to compare the oxygen evolution reaction performance of the catalysts in 0.1 M HCIO4 with a noble metal ruthenium loading of 0.096 mg cm -2 -2. Figure 5

[0045] Comparative Example 4 523 mg of Nb(HC2O4)5and 57.06 mg of H2IrCl6-6H2O were dissolved in 12 mL of H2O, and a uniform precursor solution was obtained by magnetic stirring. The solution was divided into 300 μL aliquots, which were heated in a blast drying oven at 200°C for 12 h. The resulting powder was an iridium-doped niobium oxide catalyst, and the mass percentage of iridium in the catalyst was 6.92 wt.%.

[0046] The same test method as in Example 1 was used to compare the oxygen evolution reaction performance of the catalysts in 0.1 M HCIO4 with a noble metal iridium loading of 0.096 mg cm -2 -2. Figure 5

[0047] ​​​In Comparative Example 1, pure ceria does not exhibit oxygen evolution reaction activity; in Comparative Example 3, the prepared ruthenium-doped ceria catalyst does not exhibit oxygen evolution reaction activity due to the lattice mismatch between ruthenium and cerium. In Comparative Example 2, iridium atoms in the iridium-doped ceria catalyst successfully replace cerium sites to form a stable doped phase, and the oxygen evolution reaction activity is improved compared with pure ceria and the ruthenium-doped sample, but the intrinsic activity is still not ideal due to the inherent constraints of the unit point catalytic mechanism. On this basis, the embodiment of the present application synthesizes a bimetallic doped ceria catalyst with iridium as the first metal component, and significantly improves the oxygen evolution reaction performance by utilizing the synergistic effect between the bimetallic sites, which is superior to the single-metal iridium-doped catalyst. In addition, in Comparative Example 4, the substrate is replaced with niobium oxide, and the obtained iridium-doped niobium oxide catalyst still does not exhibit oxygen evolution reaction activity, indicating that ceria as the substrate has an irreplaceable role in the system.

[0048] The above is only a few embodiments of the present application, and does not limit the present application in any form. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any skilled person in the art can make some changes or modifications to the above disclosed technical content without departing from the scope of the technical solution of the present application, which are equivalent to equivalent embodiments and belong to the scope of the technical solution.

Claims

1. A catalyst for the oxygen evolution reaction, characterized in that, The catalyst is a noble metal-doped cerium oxide catalyst, wherein the noble metal is a two-component metal, and the two-component metal is incorporated into the cerium oxide lattice in the form of single atoms, and one of the two-component metals is iridium.

2. The oxygen evolution reaction catalyst according to claim 1, characterized in that, The other metal in the binary metal composition is ruthenium, gold, or platinum.

3. The oxygen evolution reaction catalyst according to claim 1, characterized in that, The catalyst contains 3 to 7.5 wt.% iridium and 0.1 to 3 wt.% another metal.

4. A method for preparing the oxygen evolution reaction catalyst according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Disperse the dual noble metal precursor and cerium ion salt in water to obtain a precursor solution; (2) After distributing the precursor solution obtained in step (1) in equal volumes, the solvent is evaporated to obtain the oxygen evolution reaction catalyst.

5. The preparation method according to claim 4, characterized in that, In step (1), the metallic iridium precursor of the dual noble metal precursor is at least one of chloroiridium acid and iridium trichloride, and the other metallic precursor is one of ruthenium trichloride, chloroplatinic acid, and chloroauric acid. In the precursor solution, the concentration of the metallic iridium precursor is 0.01~4 mmol L. -1 The concentration of another metal precursor was 0.01–6.3 mmol / L. -1 The concentration of cerium ion salt is 82~92 mmol / L. -1 .

6. The preparation method according to claim 4, characterized in that, In step (2), the volume of the equal volume distribution is 5~300μL; The heating temperature of the evaporating solvent is 200~300℃, and the heating time is 12~24h.

7. An oxygen evolution electrode, characterized in that, The catalyst comprising the catalyst according to any one of claims 1-3 or the catalyst prepared by the preparation method according to any one of claims 4-6, is characterized in that, in the oxygen evolution electrode, the iridium loading is 0.05~0.2 mg / cm³. 2 The loading of another metal is 0.01~0.06 mg / cm³. 2 .

8. The application of the oxygen evolution electrode according to claim 7 in proton exchange membrane water electrolysis.

9. The application according to claim 8, characterized in that, The proton exchange membrane includes at least one of Nafion 117, Nafion 115, and Nafion 212.